Caprini venous thromboembolism risk assessment permits selection for postdischarge prophylactic anticoagulation in patients with resectable lung cancer - Hachey, Krista J.; Hewes, Philip D.; Porter, Liam P.; Ridyard, Douglas G.; Rosenkranz, Pamela; McAneny, David; Fernando, Hiran C.; Litle, Virginia R. (The Journal of thoracic and cardiovascular surgery, 2016)
Postoperative venous thromboembolism (VTE) creates an 8-fold increase in mortality after lung resection. About one third of postoperative VTEs occur after discharge. The Caprini risk assessment model has been used by other specialties to calculate the risk of a VTE. Patients deemed high risk by the model are candidates for prophylactic anticoagulation after discharge, reducing the VTE risk by 60%. Our primary aims were to determine the frequency of VTE events and evaluate whether the Caprini model could risk-stratify patients. Patients undergoing lung cancer resections during 2005 to 2013 were evaluated. Exclusion criteria were preoperative filter and therapeutic anticoagulation. A total of 232 patients were reviewed and Caprini scores calculated. Subjects were risk stratified into groups of low risk (0-4), moderate risk (5-8), and high risk (≥9). Occurrence of VTE events (deep vein thrombosis; pulmonary embolism) were identified by imaging. The 60-day VTE incidence was 5.2% (12 of 232); 33.3% occurred postdischarge (n = 4). Half (6 of 12) were pulmonary emboli, 1 of which caused a death, in an inpatient with a score of 16. The VTE incidence increased with Caprini score. Scores in the low, moderate, and high risk groups were associated with a VTE incidence of 0%, 1.7%, and 10.3%, respectively. With a high risk score cutoff of 9, the sensitivity, specificity, and accuracy are 83.3%, 60.5%, and 61.6%, respectively. One third of VTE events occurred after discharge. Postoperative VTE incidence was correlated with increasing Caprini scores. Patients in the high risk group had an incidence of 10.3%. Elevated scores may warrant extended chemoprophylaxis for patients after discharge.